Pengaruh Kualitas Produk, Harga Dan Gaya Hidup Terhadap Keputusan Pembelian Iphone Dengan Minat Beli Sebagai Variabel Intervening Pada Mahasiswa Unisma - Hilmi, M. Rizqi Alvan; Widarko, Agus; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The development of globalization technology and the modern world today is a necessity of human daily life, whether it is used for communication, work, or entertainment. The success factor of the company in marketing products can not only be seen from the quality, but can be seen from the price of a product. In addition, consumer behavior is also influenced by psychological factors of each person in receiving new technology and preferences of each individual. This research was carried out at Unisma Malang. The number of samples used in this study was 130 respondents. The method used in this study is the questionnaire instrument method using quantitative methods. The data analysis method to be used in this study is Structural Equation Modeling (SEM) with SmartPLS application version 4.0 and Path Analysis. The results of this study show that product quality, price and lifestyle have a significant effect on buying interest. Product quality has a significant effect on buying interest. Price and lifestyle have no effect on purchasing decisions. Product quality and buying interest have a significant effect on purchasing decisions. Product quality and price have a significant influence on purchasing decisions through buying interest. Lifestyle has no influence on purchasing decisions through buying interest. Keywords: Product Quality, Price, Lifestyle, Purchasing Decision, Buying Interest